Entretien (Criminal justice institutions and the social trajectories of adolescents/youth in Burkina Faso: endogenous/local forms and patterns of punishment, 2021)
Summary of the conditions of reception and models of punishment of adolescents/youth in conflict or in danger with the law; the conditions of their treatment and social reintegration, different forms of circulation of knowledge and models of punishment of adolescents/youth in pre- and post-colonial societies.
Keywords: Mediation; Reconciliation; Justice; Punishment; Children; Juvenile detention; Juvenile delinquency; Deprivation of Liberty; Preliminary Investigation; Investigation Phase; Enforcement of Decisions